Estudios sobre adaptacion y mejoramiento del frijol Phaseolus lunatus - Lynam, John K. (International Center for Tropical Agriculture, 1980)
Research on lima beans (Phaseolus lunatus) was conducted regarding adaptation, resistance to common bacterial blight (Xanthomonas phaseoli), resistance to leafhoppers (Empoasca kraemeri), and cyanide concn. in lima bean seed. In adaptation studies 36 climbing lima bean lines were selected from the CIAT collection on the basis of yield and freedom from diseases and planted with 6 climbing P. vulgaris lines at 5 different sites in Colombia. Av. yield of lines in all 5 sites was 2640 kg/ha. Palmira was the site with highest yields, averaging 4734 kg/ha and Monteria had the lowest yields, averaging 1646 kg/ha. Max. yield (Palmira, line G 25105) was 6121 kg/ha. Adaptation indices were calculated to compare sites and classify accession behavior. In the bacterial blight study, 189 lines were evaluated for response to inoculation in the screenhouse; 89 percent were classified as tolerant. A resistant and a susceptible line were chosen for crossing. When evaluating F2 plants a continuous segregation was found, suggesting a genetic control of a quantitative nature as in P. vulgaris. Analysis of the results was complicated due to the